Pengetahuan Dan Sikap Terhadap Perilaku Pengelolaan Sampah 3R (Reduce, Reuse Dan Recycle) Di Desa Potorono Banguntapan Bantul Daerah Istimewa Yogyakarta - Rendita Dwibarto; Sri Maulidiyatus Sa’adah (Surya Medika: Jurnal Ilmiah Ilmu Keperawatan dan Ilmu Kesehatan Masyarakat, 2022)
ABSTRACT Background of Study : Waste Garbage is one of the problems that exist in society where the impact will change people's behavior patterns. The community of Potorono Village, Banguntapan Bantul DIY has a problem with the impact of waste waste, namely the impact of waste disposal in the environment on people's behavior patterns. 3R waste management, through interviews with one of the waste bank informants, are not satisfied with the waste bank services, the community is not fully aware of waste disposal, difficulties in processing waste due to costs, lack of assistance and funds are still few, less people to make banks effective trash in the area. The purpose of this study was to determine the effect of knowledge and attitudes on waste management behavior with 3R in Potorono Banguntapan Village, Bantul DIY. Methods : This study uses an observational quantitative design with a cross-sectional approach. Data collection techniques used in this study were observation, interviews, questionnaires and documentation. And using the Total Sampling technique. The sample consisted of 30 samples of P2WKSS mothers. Data were analyzed using Chi Square.Results : The results in this study there is a significant correlation between knowledge and behavior with p value = 0.01 0.05, and there is also a significant correlation between attitudes and behavior with p value = 0.01 0, 05. Conclusion : The conclusion in the explanation is that P2WKSS women in knowledge and attitudes towards waste management with 3R are still not good. Meanwhile, the behavior of P2WKSS women towards waste management with 3R in Mertosanan Kulon Hamlet, Potorono Village Banguntapan Bantul DIY is balanced between good and bad. And after being given counseling, hopefully the insights of P2WKSS women will be wider. Keywords: Knowledge, Attitude, Behavior, Waste Management.